Radiographic evaluation of antral pseudocyst, Stafne bone cavity and elongated stylohyoid complex (Revista da Faculdade de Odontologia - UPF, 2012)
Objective: The aim of this present study was to determine the prevalence of developing lesions such as: antral pseudocyst, Stafne bone cavity and elongated stylohyoid complex in patients from the Dentistry Faculty of the Federal University of Pelotas – RS – Brazil. Methodology: A total of 667 panoramic radiographies were observed. Dome-shaped, faintly radiopaque lesions arising from the floor of the maxillary sinus were diagnosed as antral pseudocyst; yet, a stylohyoid complex was considered elongated when it presented over 30 mm length; and radiolucent cavity, unilaterally located in the posterior region of the mandible, between the mandibular angle and the third molar area, below the inferior dental canal and slightly above the mandibular basis was considered a Stafne bone cavity. Results: Fourteen cases of Antral pseudocyst were diagnosed. Most of them (93%) were unilateral, with no apparent etiology (86%). The elongated stylohyoid complex was diagnosed in 158 patients (23.68%). The Stafne bone cavity was diagnose in one patient (0.14%) only. Conclusion: It can be concluded that antral pseudocyst and Stafne bone cavity are uncommon lesions in the studied population, while the elongated stylohyoid complex was a common finding, confirming data already reported in the literature.